Green-light-induced melting of self-assembled azobenzene nano/microstructures. (20th November 2019) - Abe, Ikue; Han, Mina
Abstract : Nano/microstructures assembled from trigonal molecules with three ortho -dialkylated azobenzene wings exhibit green-light-induced melting, color tuning and fluorescence switching. Abstract : We report the formation of green-light-responsive fluorescent aggregates composed of trigonal molecules having three ortho -dialkylated azobenzene wings at the periphery (a green-light-responsive 3BuES and an aggregation-induced emission/aggregation-induced emission enhancement [AIE/AIEE]-active 3BuAz). Exposure of the respective (3BuES and 3BuAz) spheres to green light leads to color tuning and/or fluorescence switching. The results can be rationalized in terms of green-light-induced molecular conformational changes of the trigonal azobenzene molecules and the resulting phase transition of the self-assembled structures. For instance, irradiation of 3BuES with green light produces ∼35% of U-shaped cis forms ( i.e., approximately one-third of the trans -azobenzene units isomerizes to the cis forms), which seems to be sufficient to weaken the degree of the molecular packing of the trigonal azobenzene frameworks and lower the melting temperatures. Moreover, to apply the excellent fluorescence switching functions of 3BuAz aggregates to create new fluorescent organic materials, we used a co-assembly of 3BuES–3BuAz binary mixtures. Our important approach for obtaining green-light-responsive fluorescent nano/microstructures from the binary mixtures is phase separation based on the structural difference between 3BuES (having a planar central core) and 3BuAz (having a distorted conformation), which helps retain the fluorescence functions of the AIE/AIEE-active 3BuAz chromophore. Scanning electron microscopy (SEM), optical microscopy (OM), and fluorescence optical microscopy (FOM) observations prove apparent green-light-induced melting, color tuning and fluorescence switching of the phase-separated structures ( i.e., microspheres and nanoparticles).